Association Between Migraine and Dry Eye Disease: A Nationwide Population-Based Study. (3rd June 2017) - Yang, Soonwon; Kim, Woojun; Kim, Hyun Seung; Na, Kyung-Sun
ABSTRACT: Purpose : Despite the possible association between migraine and dry eye disease (DED), there are only a few studies investigating this link in a relatively limited number of patients. Therefore, we have analyzed the relationship between migraine and DED in the Korean population. Materials and Methods : This population-based cross-sectional study included 14 329 adults participating in the fifth annual Korea National Health and Nutrition Examination Survey from 2010 to 2012. Migraine, DED diagnosis, and DED symptoms were assessed using questionnaires and surveys. Data were analyzed using logistic regression to determine the association of migraine with DED while controlling for demographic, lifestyle, and medical factors. Results : Individuals with migraine were more likely to report a DED diagnosis (14.4% vs. 8.2%, p < 0.0001) and DED symptoms (22.0% vs. 15.1%, p < 0.0001). In a multivariate analysis, the association between migraine and DED diagnosis was significant after adjustments (OR, 1.577; 95% CI, 1.340–1.855). The association between migraine and DED symptoms showed a similar pattern (OR, 1.304; 95%CI, 1.151–1.502). Conclusions : Although a causal relationship was not revealed, we found that patients who had a lifetime history of migraine were more likely to suffer from DED than individuals who did not present with headaches; this association may require confirmation. Large prospective cohort studies are required to evaluate the association between migraine and DED, as well as the influence of DED treatment on the frequency and severity of migraine attacks.